Overstocking and the future of the Nojane ranches - Bekure, S.; Kgosidintsi, A. (International Livestock Centre for Africa, 1979)
Analyzes the problems of overstocking & range degradation encountered at the Nojane Ranches developed under the First Livestock Development Project in Botswana, with particular reference to stocking trends on the ranches and the financial implications of stock control as a solution to the problems.